Pelatihan Digital Marketing Pada Pimpinan Daerah Aisyiyah Lamongan - Evi Dwi Kartika Sari; Heti Nur Ani; Sawabi Sawabi; Lusi Nur Widya Wati (Pusat Riset dan Inovasi Nasional, 2021)
This article discusses social media content design training organized by the Aisyiyah Regional Leadership (PDA) Lamongan, in collaboration with the Ahmad Dahlan Lamongan Institute of Technology and Business. The main focus of the training is Instagram feed management and effective use of color. The majority of participants are women with an age range of 30-45 years. The training material includes digital marketing and the use of the Canva application. The results of this training show an increase in participants' understanding of the use of Instagram as a digital marketing tool. The high enthusiasm of the participants reflects the success of the digital marketing training organized by PDA Lamongan. By applying the knowledge gained, opportunities to hold similar activities in the future are wide open.